The Impact of Merger and Acquisition on the Financial Performance of the Nasdaq Listed Small Size Technology Companies - Rafaqat, Simon; Rafaqat, Sahil (The Economics and Finance Letters, 2020)
Merger and acquisition is a management strategy for corporate restructuring in which consolidation of companies can result in rapid business growth. The paper aims to analyze the impact of merger and acquisition on the financial performance of the business organizations in the technology sector. Therefore, the nine NASDAQ listed technology companies have been selected for this study. The financial data has been collected from the SEC, NASDAQ, and annual reports of the companies. The total study period comprises of twenty-two years ranging from 1996 to 2017. The statistical tool, Independent sample t-test, is applied on the fourteen financial ratios for four years before the merger and four years after the merger. The results of the paper show, that there is an improvement in liquidity, efficiency, and profitability, whereas the leverage ratio has deteriorated during post-acquisition. The study further examines that the profitability ratios are found to be accompanied by a more significant increase than a significant decrease in profitability ratios, and liquidity ratios found to decrease significantly more than significantly increased liquidity ratios. The cash flow has only increased significantly, whereas the leverage ratio has decreased significantly. However, the significant increase and decrease has remained equal in efficiency ratios during the post-acquisition period. In conclusion, the merger and acquisition has improved the overall financial performance. However, profitability and cash flow significantly increased, and leverage and liquidity ratios significantly declined.